Model of Family Education in Modern Era: Hamka's Perspective on Al-Azhar's Tafsir - Abd. Mukti; Syamsu Nahar; Fakrizal Fakrizal (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to determine the concept of the education system in the family through the perspective of Hamka's thought in Al-Azhar interpretation that is relevant to the conditions of the modern era. This research uses a qualitative approach with a content analysis method. The data are taken from the letters in the Qur'an which have been interpreted in the interpretation of Al-Azhar from the thought of an educational figure, namely Hamka. The data analysis procedure used in this research is qualitative content analysis. Checking the validity of this research data is done through credibility, transferability, triangulation, dependability, and confirmability. The results of the study found that 1) the purpose of family education is oriented to the happiness of the world and the hereafter, 2) the main educator in the family must have character values that can be imitated, 3) children are students in the family who must be able to grow and develop, both physically, psychological, religious, and social in navigating the life of the world and the hereafter, 4) the educational curriculum in the family is oriented to useful knowledge, 5) educational methods must be in line with the Qur'an and Sunnah, 6) evaluation of family education is built through communication between parents and children who are based on love.